Farmers' willingness to adopt organic rice farming the case in Bislig City, Surigao del Sur - Layno, Kimberly Grace V. (School of Management, University of the Philippines Mindanao, 2016)
In the Philippines, rice is a staple food and 90% consumes rice. The two most adapted rice farming method are conventional and organic farming. The local demand for organic rice in the Philippines reached up to 800 tons per month. However, there are less supply of organic rice because only few farmers adopt organic farming method. In this study, the factors that affect the farmers? willingness to adopt organic farming in Bislig City, Surigao del Sur were identified through key informant and survey interview. The logit regression analysis and profitability analysis were used to analyze the data from 146 farmers? socio-economic and other farm related indicators. Results showed that among the respondents 115 farmers (78.67%) are willing to adopt while 31 farmers (21.23% are not willing to adopt organic farming. Farmers who are willing to adopt have an average of 20 years of rice farming experience and reached 2nd year high school while farmers who are not willing to adopt have an average of 14 years of rice farming experience and reached 1st year high school level of education. Therefore, farmers who spend more years in rice farming and attained higher level of education are more willing to adopt organic farming. The factors that affect farmer?s decision to adopt organic farming are low production cost, health benefits and environment-friendly method while the factors that hinder their adoption are poor irrigation, low yield and intensive labor requirement. The ROI of the farmers who are not willing to adopt. Finally, the identified socio-economic indicators and other farm related indicators showed no significant effect on the willingness of the farmers to adopt organic rice farming in Bislig City, Surigao del Sur.